Application of the Jigsaw Learning Model to Improve Student Learning Outcomes in Mathematics - Violina Almaghfiroh; Hui Wang; Luthfiya Fathi Purposari (Universitas Muhammadiyah Mataram, 2024)
The quality of student learning outcomes in science subjects (exact), especially mathematics, is still relatively low and has always been a problem in Indonesia, namely in education. This is supported by the findings of the 2015 PISA (Program for International Student Assessment) study, which found that Indonesian students ranked 62 out of 70 countries, especially in mathematics skills. So, this study aims to improve student learning outcomes in learning mathematics, focusing on quadratic equation material. The research method used is classroom action research (CAR), applying the jigsaw-type cooperative learning model. The subject was class nine grade students of Al-Kautsar Plus Junior High School, Malang City, totaling 20 students consisting of 12 female and eight male students. Data collection using observation and test techniques. Qualitative analysis was carried out of the observation data, which contained information on student interaction. The research design consisted of planning, action, observation, and reflection. Quantitatively, the test data were analyzed, including pre and post-test scores measuring the math learning outcomes of students. The results of this study began from the beginning (pre-cycle) to cycle I, which is an increase from 50% to 65%. Then, in cycle II, there was an increase from 65% to 90% because it had met the success indicator with the number of students who scored ≥ 75 more than 80%, so it stopped in cycle II. Thus, implementing the Jigsaw-type cooperative model can improve students' learning outcomes in mathematics. In conclusion, the findings of this study show that a jigsaw-type cooperative learning model effectively improves mathematics education and teaching in secondary schools. The jigsaw model, which encourages student engagement, collaboration, and critical thinking, is a promising approach to improving mathematics education and preparing students for success in the 21st century, so it has the potential to be widely adopted in other schools by educators.